30 Extracellular vesicle metabolic protein changes during ischemic stroke - Trout, Amanda; Prince, C; Walker, M; Whitnel, L; O’ Dell, C; Frank, J; Millson, N; Al-Kawaz, M; Pahwa, S; Harp, J; Dornbos, D; Pennypacker, K; et al. (Journal of clinical and translational science, 2025)
Objectives/Goals: Ischemic stroke treatments assist in restoring blood flow, but do not guarantee good outcomes. Since extracellular vesicles (EVs) able to cross the blood brain barrier, total (nonspecific) and astrocyte enriched EVs (TEVs, AEVs, respectively) from plasma may emerge as plasma biomarkers for prognostication and targeted therapeutics. Methods/Study Population: “ Blood and Clot Thrombectomy Registry and Collaboration” (BACTRAC; NCT03153683) is a human stroke biobank at the University of Kentucky that collects samples at the time of mechanical thrombectomy during emergent large vessel occlusions (ELVO; ischemic stroke). EVs were isolated, via size exclusion chromatography, from unbanked plasma and concentrated resulting in TEVs. AEVs were immunoprecipitated with anti-EAAT1 (GLAST), an astrocyte-specific transmembrane glycoprotein. Isolated protein was sent to Olink and ran on their metabolic panel. Demographics and medical histories of the subjects were exported from REDcap and investigators were blinded during EV analysis. Results/Anticipated Results: ELVO subjects (8 females/ 5 males) were an average age of 71.1 ± 11.7 years. Lower TEV enolase 2, a neuronal glycolysis enzyme, associated with increased stroke severity (NIHSS; rs =  -0.7819, p = 0.0476). Higher systemically TEV quinoid dihydropteridine reductase (QDPR), essential co-factor enzyme, was associated with more severe strokes (NIHSS; rs =  0.8486, p = 0.0123) and lower cognition (MoCA; r2 =  0.7515, p = 0.0254). Interestingly, higher intracranial AEVs QDPR was associated with lower infarct volumes (rs =  -0.7333, p = 0.0202), less severe strokes (NIHSS; rs =  -0.6095, p = 0.0388), and better cognition (MoCA; r2 =  0.6095, p = 0.0388). Increased AEV nicotinamide adenine dinucleotide kinase another essential co-factor enzyme, intracranially also correlated to higher cognition (MoCA; rs =  0.8356, p = 0.0298). Discussion/Significance of Impact: Plasma TEV and AEV metabolic proteins correlate with the progression of stroke outcomes and should be investigated as target therapies during MT to improve outcomes.